Post-Operative Complications after Thyroid Gland Surgery due to Different Pathologic Condition: A Prospective Study - Alam, Rana Jahangir; Salim, Mohammad; Faizi, Sayem Al Monsur; Parvin, Aklima; Amina, Farah Naz; Debnath, Bidyut Chandra; Siddique, Ibrahim (Journal of Current and Advance Medical Research, 2021)
Background: The outcome and complication rates of post-operative cases are largely dependent on different factors. Objective: The objective of this study was to determine the risk factors responsible for major postoperative complications after thyroid surgery. Methodology: This was a prospective cohort study which was carried out at the Department of Surgery, Bangabandhu Shiekh Mujib Medical University, Dhaka, Bangladesh. Adult patients undergoing elective surgery for various thyroid disorders were selected as study population. This study was carried out from March 2009 to June 2011 for a period of two years. The study was included patients of various thyroid disorders that required surgical intervention of different magnitude. They were evaluated by history, physical examination, biochemical tests, ultrasound scan and FNAC where indicated. Histopathology was done and patients were followed up for subsequent outcome. Results: Among 2(2%) of them developed reactionary haemorrhage. The most common immediate surgical complication following thyroidectomy is hypocalcaemia and 12 patients (12%) experiencing this problem. 11(11%) patients developed transient tetany (hypocalcaemia) on 2nd post-operative day which was improved later on and 1(1%) patient developed permanent hypoparathyroidism and the patient supplemented by vitamin-D more than 6 months follow-up . In this study the mortality rate is 0% and complication rate is acceptable in comparison to other study. Conclusion: Hypoparathyroidism is a relatively common complication after thyroid surgery. Journal of Current and Advance Medical Research, July 2021;8(2):119-124